Catalytic anode used for electrochlorination and method
The catalytic anode structure with a composite metal layer of cobalt oxide, ruthenium, and tin oxide addresses durability and efficiency issues in chlorine generation, offering cost-effective and long-lasting performance.
Patent Information
- Application Number
- JP2024099006
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-20
- Filing Date
- 2024-06-19
- Publication Date
- 2025-01-28
AI Technical Summary
Existing catalytic anodes for chlorine generation in electrolytic cells face issues with durability, mechanical adhesion, and efficiency due to the use of expensive precious metals like iridium, and suffer from cracks that lead to corrosion and reduced performance over time.
A catalytic anode structure using a composite metal layer composed of cobalt oxide particles, ruthenium, and tin oxide, applied on a titanium substrate, which provides high catalytic activity, selectivity, and durability, avoiding the need for expensive precious metals.
The anode structure achieves high electrical efficiency with low overvoltage, improved mechanical adhesion, and extended operational life, while reducing costs by using less expensive materials.
Smart Images

Figure 2025013751000006 
Figure 2025013751000007 
Figure 2025013751000008
Abstract
Description
[Technical field]
[0001] The present invention relates to catalytic anodes for use in electrochlorination systems for producing chlorine from aqueous solutions containing chloride ions via a chlorine evolution reaction. Such chlorine generation systems are particularly useful in ballast water treatment systems and in the industrial treatment and purification of wastewater, such as industrial and municipal waters. They can also be used for the industrial production of chlorine, particularly in the chlor-alkali process. [Background technology]
[0002] The chlorine evolution reaction ("CER") is a well-known reaction in industrial chemistry and has found applications in both large-scale production of chlorine for capture and immediate application. In the chlor-alkali process, chlorine and sodium hydroxide are produced by electrolysis of aqueous sodium chloride solution, and the products are recovered for further industrial use. Chlorine is an effective biocide, and therefore electrochlorination systems are used independently for water purification based on the in situ generation of aqueous chlorine and its biocidal effect. Microbially contaminated water can be effectively treated by electrochlorination, which has applications in various scenarios, such as industrial wastewater and general water disinfection. In addition, an increasing number of ships are being equipped with on-board ballast water treatment systems to treat ballast tank water before discharge. Ships traveling long distances may introduce invasive aquatic organisms into local ecosystems by discharging ballast water collected in remote areas. Invasive invasive species can have a significant impact on local ecosystem balance. Ship-mounted generator-powered electrochlorination systems provide an effective and immediate solution to treat such water before discharge. Effective industrial use of electrochlorination systems and methods relies on electrolysis cells that can operate efficiently for extended periods of time. To promote chlorine production at the anode, it is common in the art to apply a catalytic coating to the electrolyte-facing surface of the anode to catalyze the chlorine evolution reaction. Such catalytic coatings typically contain significant amounts of one or more precious metals, the most commonly used of which are iridium and ruthenium, which add significant cost and complexity to anode manufacture. There remains a continuing need in the art for new catalytic anodes that can more cost-effectively meet the various technical considerations associated with industrial or municipal electrochlorination environments. When selecting a catalytic coating for an electrochlorination anode, various technical considerations must be taken into account.
[0003] First, the catalyst selected must be sufficiently selective to the chlorine evolution reaction to reduce efficiency losses resulting from the competing oxygen evolution reaction, which may otherwise occur at the anode due to the electrolysis of water in aqueous solution. Second, the catalyst coating must be durable enough to withstand long-term operation and the acidification of the electrolyte that may occur during electrochlorination. Durability also requires good mechanical adhesion between the catalyst and the anode substrate surface. Third, the anode coating should be highly conductive to improve electrical efficiency by avoiding the need for large overpotentials to drive the electrolysis cell. Indeed, it is clear that some overpotentials typically occur with efficiency losses in electrolysis cells, but a lower degree of overpotential provides an important relative efficiency gain, and maintaining a lower overpotential over long-term operation provides another relevant indicator of electrode durability and service life. The physical durability of the catalytic coating on the anode can be evaluated both by its performance in long-term tests and, most preferably, by examining its morphology with a scanning electron microscope. Indeed, catalytic anode coatings in the art typically exhibit an external surface morphology resembling a dry lake bed, with the appearance of fine sedimentary deposits widely interrupted by characteristic "mud cracks", as shown in Figure 1. These cracks create weaknesses in the catalytic layer, allowing electrolyte and reactive species to penetrate toward the anode's substrate, weakening the bond between the catalyst and the substrate and resulting in a degradation process in which the exposed composition corrodes. Typically, this results in a loss of electrical efficiency (e.g., as manifested by an increase in overpotential) and a loss of catalytic activity, reducing the useful life of the anode and leading to expensive replacement. Summary of the Invention
[0004] The catalytic anode of the first aspect of the invention, obtainable by the method of the second aspect of the invention, offers an advantageous balance of properties that address the technical requirements of such an anode, while avoiding the need for expensive precious metals, particularly iridium. In particular, the catalyst coated anode structure defined in the first aspect of the invention exhibits high catalytic activity and selectivity for the chlorine evolution reaction, excellent durability in terms of operational life and mechanical adhesion between the catalyst and the anode surface, and improved resistance to acids formed during operation. The catalyst coated anode structure defined in the first aspect of the invention also has high anode conductivity, resulting in efficient electrical operation without excessive overpotentials, which is maintained over long periods of operation.
[0005] These advantages of the first aspect of the invention are provided by applying on the electrolyte-facing surface of the anode a conductive composite metallurgical layer of defined morphology and composition, which composite layer comprises a specific structural base composition for supporting a catalyst, and a specific catalyst composition essentially comprising crystalline cobalt oxide particles. The characteristic morphology and chemical composition of this composite metallurgical layer is best achieved by a preparation method employing control of reactants and process conditions as further defined in the second aspect of the invention. The present invention therefore provides in a first aspect a catalytic anode structure for use in an electrochlorination system comprising an electrically conductive solid substrate overlaid on its surface facing an electrolyte with an electrically conductive composite metallurgical layer, the layer comprising: A structure-based composition for coating a substrate surface, the structure-based composition having the form of void-interspersed aggregate particles and comprising metal oxide compounds of ruthenium, tin and titanium; and A catalyst composition comprising cobalt oxide crystalline particles distributed on the top surface and within the voids of a structure-based composition. Including, cobalt is present in an amount of at least 12.5 atomic % of the total metal atomic content of the composite metallurgical layer, and ruthenium and tin are present in the composite metallurgical layer in amounts that provide a total metal stoichiometric ratio of Ru:Sn of 1:≧1 based on the total content of ruthenium and tin in the composite metallurgical layer; The outer surface of the composite metallurgical layer has the form of a continuous coating of agglomerated particles; A catalytic anode structure is provided.
[0006] In the anode of the first embodiment, the catalyst composition preferably further comprises one or more noble metals or oxide compounds thereof, and particularly preferably further comprises ruthenium or an oxide thereof. As used herein, the term "atomic % of the total metal atomic content" with respect to a particular metal in a composition refers to the number of atoms of that metal present in the relevant composition, expressed as a percentage of the total number of atoms of the metal element present in the relevant composition, regardless of whether such metal element is present in elemental form or in the form of a compound. As used herein, the term "overall metallic stoichiometric ratio" of a particular metallic element refers to the stoichiometric ratio of all atoms of such metallic element present in a composite metallurgical layer (or other composition, if applicable), regardless of whether such metallic element is present in elemental or compound form. For example, in a structure containing 15 atomic % ruthenium and 15 atomic % tin purely in elemental form, the overall metallic stoichiometric ratio of Ru:Sn is 15:15, i.e., 1:1, and in a structure containing 15 atomic % ruthenium in the form of elemental ruthenium, and 15 atomic % elemental tin, and further compounded 15 atomic % tin in the form of an oxide, the overall metallic stoichiometric ratio of Ru:Sn is 15:(15+15), i.e., 1:2.
[0007] The term "morphology" is used herein to describe the three-dimensional structure and appearance of the material in question. Morphology can be most usefully determined by scanning electron microscopy, as described herein below, which provides a three-dimensional image of the surface of the material so as to allow direct visual appreciation of its structure and appearance. Preferably, the morphology of the structural base composition is interspersed with sufficient voids to render the base composition porous to the catalyst composition, allowing the catalyst composition to penetrate particularly extensively through the thickness of the base composition upon application. Also within this specification, the term "continuous coating" in relation to the first aspect of the invention is used to describe a coating that completely covers the underlying material. Preferably, this continuous coating is not interrupted by significant cracks or other through discontinuities that weaken its integrity. In particular, the continuous coating of the first aspect of the invention does not exhibit the extensive "mud crack" precipitate morphology of conventional catalytic coatings used in electrochlorination, but instead provides a continuous surface coating or layer composed of a three-dimensional matrix of agglomerated particles as viewed under a scanning electron microscope. The present invention is based in part on the discovery that by combining a specific structural base composition, which includes tin in combination with ruthenium and titanium, coating the surface of the anode substrate, with an overlayer CER catalyst composition essentially based on cobalt oxide, an anode structure with excellent properties for obtaining a CER reaction in electrochlorination can be advantageously obtained. The resulting composite metallurgical layer on the anode provides the anode with a surface chemistry and an advantageous morphology that achieves excellent durability in terms of operating life and mechanical adhesion between the catalyst and the anode substrate, and provides advantageous catalytic activity and selectivity for the chlorine evolution reaction. The composite metallurgical layer also provides the anode with high resistance to acid corrosion and high conductivity, which translates into high electrical efficiency and long-term operating performance at low overpotentials. The use of a catalyst composition based mainly on cobalt oxide instead of a higher amount of precious metal, combined with the use of tin in the structural base composition, also makes it possible to achieve this anode performance at a significantly lower cost than conventional catalytic anodes based mainly on iridium and / or ruthenium.
[0008] In particular, the structural base composition essentially comprises a combination of ruthenium, tin, and titanium in the form of metal oxides, and the presence of a minimum percentage of ruthenium in combination with titanium, and the co-presence of tin in a stoichiometric amount equal to or exceeding the amount of ruthenium, provides a base composition capable of forming structures having the morphology of agglomerated particles interspersed with voids, as further shown herein below. In contrast to the conventional thinking in the art regarding barrier layers, the particulate morphology of the structural base composition contributes to improved mechanical adhesion between the composite metallurgical layer and the substrate. This particulate base composition also improves the structural foundation of the catalytic composition on the anode, and the voids of the base composition, in addition to the continuous coating of its outer surface, allow the catalytic composition to penetrate deep into the structural base layer, resulting in a highly adherent composite metallurgical layer on the electrolyte-facing surface of the anode, which has the highly advantageous combination of properties described above for the chlorine evolution reaction. The use of a defined composition comprising oxides of ruthenium, tin, and titanium as the structural base layer of the overlying catalyst composition contrasts with the prior art use of one or more such oxides as the primary catalytic component of the catalyst composition, which instead relies on the specific morphology of the defined base composition to provide structural integrity to the composite metallurgical layer and support the overlying cobalt-based catalyst composition.
[0009] In addition, the cobalt oxide crystalline particles distributed on the top surface and within the voids of the structure-based composition serve as the essential catalytic species of the composite metallurgical layer, providing highly selective catalysis for the CER reaction at a significantly lower cost than precious metal-based catalytic compositions such as iridium-based compositions. Although the essential cobalt oxide catalyst of the present invention may be supplemented with catalytic precious metal oxides, cobalt should be present in an amount of at least 12.5 atomic % of the total metal atom content of the composite metallurgical layer and should be the predominant catalytic species in the catalytic composition. This use of cobalt oxide as the predominant catalytic species is made possible by its combined use with the defined structure-based composition, which combination serves to provide a highly selective, durable and efficient cobalt oxide-based catalytic anode for CER with the balance of improved properties described above.
[0010] The agglomerated particles on the outer surface of the composite morphological layer are also essential to provide a highly effective and available surface area for catalytic activity. In particular, this particulate morphology overcomes the mass transport limitations of conventional lake bed precipitate catalyst layers, allowing the catalytic anode of the first aspect of the invention to operate at higher efficiency for the chlorine evolution reaction, contributing to various advantages of the invention. The efficiency advantage of the catalytic anode of the present invention in the chlorine evolution reaction is particularly exhibited by aqueous solutions of chloride ions having low salt levels (e.g., brine). The improved efficiency at low salt levels makes the electrode more suitable for a wide range of water treatment applications, such as municipal water applications or drinking water treatment, in addition to wastewater treatment and other chlorination applications. The improved efficiency also results in reduced levels of unwanted electrolysis by-products, such as chlorate and perchlorate ions. In a preferred form of the catalytic anode of the first embodiment, the catalytic composition of the composite metallurgical layer does not contain titanium or compounds thereof. Such titanium-free catalytic composition provides the resulting anode with the additional advantage of being highly suitable for use in current reversal cells. Current reversal has become an easy-to-maintain means of removing deposits of metals such as calcium and magnesium that may otherwise accumulate on the cathode during long-term electrolysis operation, especially for treating municipal or residential water, such as pools with low salt levels. However, conventionally, current reversal inside a cell causes more rapid deterioration and damage of the anode catalytic coating, since significant pH fluctuations occur at the surface of the electrode, especially within the crack surfaces of the "mud crack" catalyst, and electrolyte may become saltwater depleted, thus allowing competing water splitting reactions to occur more widely. Titanium present in the coating is easily dissolved in this environment, leading to weakening of the catalytic coating on the substrate and rapid deterioration of the coating and performance. The present invention provides an anode that can eliminate the presence of titanium in the catalytic composition due to its high efficiency, thereby avoiding this deterioration and resulting in a longer anode life, especially in current reversal environments.
[0011] Such titanium-free catalyst compositions also provide the resulting anode with the added advantage of greater resilience in the high salt level chlor-alkali process. Typically, chlor-alkali cells are characterized by a Teflon or similar membrane disposed between the cathode and anode. Caustic solutions inside the cell can cause the membrane to perforate, allowing the caustic solution to reach the anode, causing corrosion and depletion of titanium. The present invention provides an anode that, due to the high efficiency of the catalyst composition, can eliminate the presence of titanium in the catalyst composition, thereby avoiding this degradation and resulting in longer anode life in this environment. Formation of the catalytic anode structure of the first aspect of the present invention is best achieved by a method of sequential addition of the structural base composition and the catalyst composition under process conditions ideally favoring the formation of the proper morphology of the base composition and composite metallurgical layer.
[0012] The present invention therefore provides in a second aspect a method for preparing a catalytic anode structure for use in an electrochlorination system, comprising the following sequence of steps: a) providing or obtaining a conductive solid substrate; b) providing on the electrolyte-facing surface of the substrate a conductive metallurgical composition (i), the composition (i) having a total metal stoichiometry of Ru ≧0.3 (Sn+Ti) ≦0.7 applying an electrically conductive metallurgical composition (i) comprising compounds of ruthenium, tin and titanium in an amount to provide c) optionally applying to the metallurgical layer resulting from the application of composition (i) a conductive metallurgical composition (ii) comprising one or more ruthenium compounds; and (d) applying an electrically conductive metallurgical catalyst precursor composition (iii) comprising cobalt oxide crystalline particles to the metallurgical layer resulting from the application of composition (i) or resulting from the application of compositions (i) and (ii), with composition (ii) optionally being applied thereto. Including, the process solvent used to apply the metallurgical composition in steps (b) and (d) and optionally step (c) is a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5; The resulting structure is then dried and then heat treated at a temperature of at least 450 ° C. A method is provided.
[0013] The process of the second aspect is particularly characterized by the use of particular starting metallurgical compositions and preparation conditions that result in the anode structure of the first aspect. First, starting composition (i) is provided with a total metal stoichiometry of Ru ≧0.3 (Sn+Ti) ≦0.7 The use of a conductive metallurgical composition (i) comprising compounds of ruthenium, tin, and titanium in amounts providing, under the process conditions of the second aspect, results in a structural base layer of the composite metallurgical layer of the anode that provides an advantageous substrate for the overlayer catalyst composition. The defined total metal stoichiometry of the starting composition (i) results in the desired morphology of the resulting structural base layer, in particular a layer having the morphology of agglomerated particles interspersed with voids. This formation of the desired base composition morphology is further promoted by the use of defined process solvents and, in some preferred embodiments, by heating the anode substrate to a temperature in the range of 50-200° C. during application step (b). The use of a process solvent during application step (b), which is volatile under the conditions, further allows for the formation of voids in the structural base layer, which can be advantageously penetrated by the subsequent catalyst composition (iii) applied in step (d) (and optional composition (ii) applied in step (c)). This solvent also results in the simultaneous loss of a certain proportion of the more volatile metal salts contained within the defined metallurgical content of starting composition (i), resulting in the formation of a metallurgical layer having a different total metal stoichiometry with respect to ruthenium, tin, and titanium than starting composition (i). It is believed that the use of a defined composition (i) and defined process conditions advantageously adjusts this simultaneous metal salt volatility loss, resulting in the formation of an applied metallurgical layer having a desired composition and morphology.
[0014] The use of a specified process solvent during application step (d) (and optional application step (c), if present), followed by heat treatment of the resulting structure also contributes to the formation of advantageous morphology and composition of the resulting composite metallurgical layer on the anode of the present invention. In a preferred embodiment, it has been found that the formation of the desired composite metallurgical layer on the anode is further enhanced by applying metallurgical compositions (i) and (iii) (and composition (ii), if present) to a substrate that is heated to a specified temperature range of 50 to 200° C. during the application step (and preferably throughout the entire application step). It has also been found that drying the resulting structure within the same temperature range of 50-200°C further enhances the formation of the desired composite metallurgical layer, particularly by favoring the formation of the desired morphology, that is, a continuous layer uninterrupted by mud cracks or other significant through-hole discontinuities.
[0015] Importantly, it has been found that a final heat treatment of the resulting structure at a temperature of at least 450°C is essential to enhance the formation of the desired composite metallurgical layer, in particular by favouring improved mechanical adhesion between the composite metallurgical layer and the anode substrate, and by favouring high selectivity for the chlorine evolution reaction over the oxygen evolution reaction via water splitting. In this regard, in the second aspect of the invention, a final heat treatment in the range of 450-600°C, and in particular an optimum final heat treatment at 500°C, is preferred, where higher selectivity for the chlorine evolution reaction and mechanical adhesion are observed. In the second aspect of the invention, the use of a specified process solvent for applying the metallurgical composition in steps (b) and (d) and optionally step (c) is also essential, the process solvent being a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5, preferably in a volume ratio range of 82.5:17.5 to 87.5:12.5. Most preferably, the process solvent is a mixture of isopropanol and water in a volume ratio of 85:15. It has been found that this composition of the process solvent exhibits advantages over similar alcoholic solvents in terms of the dissolving power of the starting compounds used in the method of the second aspect. In addition, it has been found that this composition of the process solvent is advantageous for controlling the surface morphology of the layer formed by the application of the metallurgical composition, both before and after the final heat treatment step, and in particular contributes to an agglomerated particulate morphology of the structure-based composition free of integrity-weakening cracks. This ability to control the layer morphology is due in particular to the choice of alcohol and the ratio of alcohol to water in the process solvent, with control being optimal at a volume ratio of 85:15 (isopropanol:water).
[0016] Further aspects of the invention are also described herein below, An electrochlorination system comprising an electrolytic anode structure obtainable by the method of the first or second embodiment, and An electrolytic method for catalytically generating chlorine gas from an aqueous solution containing chloride ions, comprising the step of passing an electric current through said solution in an electrolytic cell comprising an electrolytic anode structure obtainable by the method of the first aspect or of the second aspect, at the anode chlorine gas is generated from the aqueous solution. Includes. In a preferred embodiment of the electrolysis process, the chlorine gas generated by the process is used as a biocide to disinfect water, more particularly to disinfect ballast water, or industrial wastewater, or municipal or domestic water, such as recreational water for swimming pools and domestic drinking water. In an alternative preferred embodiment, the process is a chlor-alkali process for the production and recovery of chlorine. The invention will now be described in more detail as follows.
[0017] This application includes the following figures: [Brief description of the drawings]
[0018] [Figure 1] Figure 1: A diagram illustrating the lake bed morphology of a conventional catalyst bed with extensive "mud cracks". [Diagram 2] FIG. 2: A diagram showing the aggregate particulate morphology of a preferred embodiment of the present invention. [Diagram 3] FIG. 3: TOF-SIMS (Time-of-Flight Secondary Ion Mass Spectroscopy) concentration-depth profile of a preferred embodiment of the present invention. [Figure 4] FIG. 4: TOF-SIMS (Time-of-Flight Secondary Ion Mass Spectroscopy) concentration-depth profile of a preferred embodiment of the present invention. [Diagram 5] FIG. 5: Anode life test - shows the effect of ruthenium stoichiometry in composition (i) of the present method on structural base composition durability. [Figure 6] FIG. 6: Anode life testing - effect of structural base metal composition. [Figure 7-1] 7(a), (b) and (c): Scanning electron microscope (SEM) examination of the comparative base composition after application to a substrate. [Figure 7-2] 7(a), (b) and (c): Scanning electron microscope (SEM) examination of the comparative base composition after application to a substrate. [Figure 8] FIG. 8: A diagram illustrating the improvement in anode life due to the presence of a base structural layer. [Figure 9] FIG. 9: A diagram illustrating a further advantage of applying optional composition (ii) to the anode according to the method of the present invention. [Figure 10] FIG. 10: A diagram illustrating the anode life improvement by including tin and antimony, preferably in a defined stoichiometry, in composition (iii) of the present method. [Figure 11]FIG. 11(a) and (b): CER efficiency and lifetime improvement by including tin and antimony in defined stoichiometry in composition (iii) of the present method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] First aspect of the present invention (catalytic anode) The catalytic anode structure of the first embodiment comprises an electrically conductive solid substrate having an electrically conductive composite metallurgical layer overlaid on its electrolyte-facing surface, the layer comprising: A structural base composition for coating a substrate surface, the structural base composition having the form of agglomerated particles interspersed with voids, the structural base composition comprising metal oxide compounds of ruthenium, tin, and titanium; and Catalyst composition comprising cobalt oxide crystalline particles distributed on the top surface and within the voids of a structure-based composition - Patents.com Including, cobalt is present in an amount of at least 12.5 atomic % of the total metal atomic content of the composite metallurgical layer, and ruthenium and tin are present in the composite metallurgical layer in amounts that provide a total metal stoichiometric ratio of Ru:Sn of 1:≧1 based on the total content of ruthenium and tin in the composite metallurgical layer; The outer surface of the composite metallurgical layer has the form of a continuous coating of agglomerated particles. The anode structure of the first aspect of the invention is obtainable, and preferably obtained, by the process of the second aspect of the invention. The anode structure of the first embodiment has the distinction that the outer surface of the composite metallurgical layer has the morphology of a continuous coating of agglomerated particles. The presence of occasional cracks or other surface discontinuities or fault lines is not excluded from this broadest scope of the first embodiment, so long as such imperfections do not penetrate beyond the catalyst composition to the depth of the metallurgical layer or expose the underlying substrate to electrolytic corrosion. Preferably, however, the anode structure of the first embodiment has a composite metallurgical layer having an outer surface morphology of a continuous, crack-free coating of agglomerated particles.
[0020] The agglomerated particle morphology of the outer surface of the composite metallurgical layer contrasts with the extensive crack-precipitate-like surface morphology of conventional catalytic anodes and can be best visualized by examination under a scanning electron microscope, as shown in the accompanying figures. In each case, scanning electron micrographs were obtained using a JSM-IT500 InTouchScope™ scanning electron microscope instrument, using the settings described in the associated figure legend. In Figure 1, scanning electron microscopy of the exterior surface morphology of a conventional catalytic anode for electrochlorination reveals a characteristic "mud-crack" appearance with extensive deep cracks extending throughout the deposit-like surface coating. Such a morphology renders the catalytic surface susceptible to chemical attack, weakening its structural integrity and reducing its life and usefulness. In contrast, in FIG. 2, scanning electron microscopy at the indicated magnification shows a characteristic surface of a preferred catalytic anode of the first embodiment, having a continuous, crack-free surface layer and an aggregated particulate morphology.
[0021] An essential element of the anode structure of the first embodiment is the presence of cobalt oxide present in an amount of at least 12.5 atomic % of the total metal atomic content of the composite metallurgical layer. The anode of the present invention provides excellent durability in terms of operating life and mechanical adhesion between the catalyst and the anode substrate, high resistance to acid corrosion, and high conductivity, providing a means to apply to the anode high levels of a highly selective form of cobalt oxide-based catalyst for electrochlorination, which leads to high electrical efficiency and low overpotential operating performance. The use of catalytic compositions based on cobalt oxide instead of precious metals as the primary catalytic metal can also enable this anode performance at a significantly lower cost than conventional precious metal-based catalysts such as iridium-based catalytic anodes. Preferably, in the anode structure of the first aspect, cobalt oxide is present in the highest amount practical to maximize its catalytic effect while still obtaining other advantages of the invention. Accordingly, it is preferred that cobalt is present in an amount of at least 15 atomic % of the total metal atomic content of the composite metallurgical layer, more preferably at least 20 atomic % of the total metal atomic content of the composite metallurgical layer. Even more preferably, cobalt is present in an amount of at least 30 atomic % of the total metal atomic content of the composite metallurgical layer, and most preferably at least 40 atomic % of the total metal atomic content of the composite metallurgical layer. Ideally, cobalt is present in an amount of 50-80 atomic % of the total metal atomic content of the composite metallurgical layer, optionally within the range of 60-75 atomic % of the total metal atomic content of the composite metallurgical layer. Such a cobalt content is advantageously achieved by preparing the anode structure according to the method of the second aspect of the invention.
[0022] It is also essential to the present invention that ruthenium and tin are present in the composite metallurgical layer in amounts that provide a total metal stoichiometric ratio of Ru:Sn of 1:≧1 based on the total content of ruthenium and tin in the composite metallurgical layer. An important finding of the present invention is that the use of a total stoichiometric amount of tin at least equivalent to the amount of ruthenium is advantageous, which can significantly reduce the total ruthenium content of the electrode coating while also contributing to the advantageous combination of properties exhibited by the composite metallurgical layer of the present invention. In particular, the presence of the specified amount of tin promotes the mechanical integrity of the layer and its electrical conductivity. The total metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is preferably 1:≧1.5, more preferably 1:≧2. Even more preferably, the total metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is 1:≧3, most preferably 1:≧5. The optimum value of this ratio in the present invention is in the range of 1:8 to 1:20, for example in the range of 1:8 to 1:15.
[0023] The above preferred ranges of cobalt content and Ru:Sn total metal stoichiometry in the composite metallurgical layer can be combined for optimum effect in the anode structure of the first aspect of the invention. In particular, a more preferred embodiment of the first aspect comprises: 1) Cobalt is present in an amount of at least 15 atomic % of the total metal atomic content of the composite metallurgical layer, and the total metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is 1:≧1.5, more preferably 2) The anode structure of the first aspect, more preferably wherein cobalt is present in an amount of at least 20 atomic % of the total metal atomic content of the composite metallurgical layer and the total metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is 1:≧1.5, or more advantageously 1:≧2. 3) The anode structure of the first aspect, more preferably wherein cobalt is present in an amount of at least 30 atomic % of the total metal atomic content of the composite metallurgical layer, and the total metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is 1:≧1.5, or more preferably 1:≧2, most preferably 1:≧3. 4) The anode structure of the first aspect, most preferably wherein cobalt is present in an amount of at least 40 atomic % of the total metal atomic content of the composite metallurgical layer, and the total metal stoichiometry of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is 1:≧1.5, or more preferably 1:≧2, most preferably 1:≧3, ideally 1:≧5. 5) The anode structure of the first aspect, wherein cobalt is present in an amount of 50-80 atomic % of the total metal atomic content of the composite metallurgical layer, and the total metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is 1:≧1.5, or more preferably 1:≧2, most preferably 1:≧3, and ideally 1:≧5. Includes.
[0024] Particularly preferred anode structures of the first embodiment are those in which cobalt is present in an amount of at least 40 atomic % of the total metal atomic content of the composite metallurgical layer, and ruthenium and tin are present in the composite metallurgical layer in amounts providing a total metal stoichiometric ratio of Ru:Sn of 1:≧5 based on the total content of ruthenium and tin in the composite metallurgical layer. An optimal anode structure for the first embodiment is one in which cobalt is present in an amount between 50 and 80 atomic % of the total metal atomic content of the composite metallurgical layer, and ruthenium and tin are present in amounts to provide the composite metallurgical layer with a total metal stoichiometry of Ru:Sn of 1:≧5, optimally in the range of 1:8 to 1:15, based on the total ruthenium and tin content in the composite metallurgical layer. The individual metal contents and total metal stoichiometry of the composite metallurgical layer can be measured by known techniques using ICP-MS (Inductively Coupled Plasma Mass Spectroscopy) to determine the compositional characteristics of the present invention. In the anode structure of the first aspect, the cobalt oxide crystalline particles in the catalyst composition preferably consist essentially of crystalline cobalt oxide having the formula Co3O4. In one such embodiment, such cobalt oxide crystalline particles may consist of crystalline cobalt oxide having the formula Co3O4. The presence of this crystalline form of cobalt oxide can be confirmed by X-ray diffraction or other conventional crystallographic techniques. The Co3O4 crystalline particles can be sized by directly measuring their diameter in transmission electron micrograph images, with the diameter preferably being in the range of 1 nm to 20 nm, more preferably 1 nm to 10 nm, and most preferably 3 nm to 7 nm.
[0025] In the anode of the first embodiment, the catalyst composition preferably further comprises one or more precious metals or oxide compounds thereof, and in particular ruthenium or an oxide thereof. For the purposes of the present invention, the amount of any included precious metal should be small enough so as not to reduce the cobalt content of the composite metallurgical layer below the level defined by the present invention, and preferably the amount of precious metal should not exceed 10 atomic %, more preferably not exceed 5 atomic %, of the total metal atomic content of the composite metallurgical layer. In a more preferred embodiment, the cobalt oxide crystalline particles in the catalyst composition consist essentially of crystalline cobalt oxide having the formula Co3O4 and further consist essentially of ruthenium or its oxides at a level of up to 5 atomic % ruthenium based on the total metal atomic content of the crystalline particles, at least a portion of said ruthenium preferably being present on the crystalline particles in the form of a surface decoration. In this latter embodiment of the anode, the cobalt oxide crystalline particles in the catalyst composition, in addition to the surface decoration, may further comprise crystalline regions in which ruthenium is incorporated within the crystal lattice of the cobalt oxide or forms a mixed metal oxide with cobalt, or both. In such embodiments, the limited amount of ruthenium provided in the catalyst composition associated with the cobalt oxide crystalline particles provides the advantage of further improving the properties of the composite metallurgical layer on the anode, most notably improving the selectivity of the catalyst for the chlorine evolution reaction and improving the durability of the anode, especially in terms of operating life. The ruthenium may be present in the form of an oxide compound or in the form of a metallic element, at least when incorporated within the crystal lattice of the cobalt oxide. In such embodiments, the ruthenium associated with the cobalt oxide catalyst may be present in a total non-stoichiometric proportion approaching a mixture of elemental ruthenium and oxide-bound ruthenium.
[0026] However, it has been found that if the ruthenium content in the crystalline particles of the catalyst composition exceeds the upper limit of 5%, it leads to a decrease in the efficiency of the chlorine evolution reaction, as manifested by a decrease in the low salt efficiency, especially in the case of water treatment applications.For this reason, the ruthenium content associated with the cobalt oxide catalyst particles should be limited to the levels described, and it is not advantageous to further increase the ruthenium content in the hope of any further improvement. In all the above embodiments of the anode of the first aspect, the composite metallurgical layer comprises a catalyst composition comprising cobalt oxide crystalline particles distributed on an upper surface and within the voids of the structural base composition. The catalyst composition preferably consists essentially of cobalt oxide crystalline particles distributed within a matrix of another metal oxide, particularly a crystalline matrix of another metal oxide, and in particular the other metal oxide preferably does not comprise a substantial or any amount of a precious metal oxide such as palladium or iridium other than those defined herein for the present invention.
[0027] In particular, in all embodiments of the anode, the catalytic composition preferably comprises, and preferably consists essentially of, cobalt oxide crystalline particles within a crystalline matrix of antimony and tin oxides, and the catalytic composition is preferably present on the top surface and within the voids of the structural base composition. In such embodiments of the anode, the total metal stoichiometry of cobalt:total antimony and tin in the composite metallurgical layer is preferably in the range of 2:1 to 9:1. More preferably, the total metal stoichiometry of cobalt:total antimony and tin in the composite metallurgical layer is in the range of 2.5:1 to 6:1, and most preferably in the range of 3:1 to 5:1. Optimally, the composite metallurgical layer is in the range of 3:1 to 4:1. Surprisingly, it has been found that such total metal stoichiometry of cobalt:total antimony and tin in the composite metallurgical layer provides advantageous performance. By maintaining this ratio within the basic ranges described above, the durability of the catalytic anode is improved, which is manifested by an increase in useful operating life. This increase in life provides highly advantageous performance to the anode of the first aspect.
[0028] In the above anode embodiments, it is also more preferred that the compounds of antimony and tin which serve as a matrix in the catalyst composition are present in an amount to provide a total metal stoichiometric ratio of antimony:tin in the composite metallurgical layer in the range of from 1:5 to 1:200, preferably in the range of from 1:5 to 1:100. In this regard, it has further surprisingly been found that the total metal stoichiometry of antimony:tin in the composite metallurgical layer provides an additional contribution to obtaining optimal anode performance: maintaining this total metal stoichiometry within the above range provides the anode with a further improved operational life, and also improves the CER efficiency of the cell, as evidenced by the faradaic efficiency. In this regard, the antimony and tin compounds are preferably present in the composite metallurgical layer in an amount that provides a preferred total metal stoichiometric ratio of antimony:tin in the range of 1:25 to 1:100, most preferably in the range of 1:30 to 1:85.Optimally, this ratio may be in the range of 1:50 to 1:85, and in superior embodiments, 1:75 and 1:84.
[0029] In each of the above embodiments of the anode structure, the composite metallurgical layer preferably further comprises at least one palladium compound in an amount to provide a total palladium content of up to 7 atomic % of the total metal atomic content of the composite metallurgical layer. The introduction of limited amounts of palladium into the composite layer is preferably achieved by including one or more palladium-based compounds in the catalyst composition or by subsequent doping. Palladium provides an even further improvement in chlorine evolution reaction efficiency, particularly for water treatment applications, as evidenced by an increase in low salt efficiency. However, when the palladium content in the catalyst composition exceeds the upper limit of 7 atomic %, no further improvement in the efficiency of the chlorine generation reaction is achieved, as evidenced by no further increase in the low salt efficiency, particularly in the case of water treatment applications. For this reason, the palladium content associated with the cobalt oxide catalyst particles should be limited to the levels described in order to avoid unnecessary cost and complexity. It is preferred that the total palladium content is at most 5 atomic % of the total metal atomic content of the composite metallurgical layer, more preferably at most 3 atomic %, and optimally, the total palladium content is at most 1.5% of the total metal atomic content of the composite metallurgical layer.
[0030] The anode of all embodiments of the first aspect essentially consists of a conductive solid substrate, which substrate is known in the art. This substrate preferably essentially consists of valve metals such as titanium, zirconium, niobium, and tantalum (and alloys / mixtures containing these metals), and preferably titanium, most preferably titanium. Mixtures of valve metals may also be present in the substrate. Oxides of one or more valve metals essentially present in the substrate may be further observed or produced as artifacts under the conditions of anode manufacture and use, especially at the surface of the substrate or at the interface with the composite metallurgical layer, and their presence is not excluded from the substrate of the present invention, unless they form the main component of the substrate. Anode substrates can be produced by conventional means in the art, purchased or custom manufactured, and formed into any shape suitable for end use as an anode in an electrochemical cell or system. In particular, substrates can be formed into meshes, plates, and more complex three-dimensional shapes such as cylinders. Substrates may be coated on one or more sides with complex metallurgical layers depending on their design and configuration. In the anode of all embodiments of the first aspect, the distribution of the cobalt oxide-based catalytic composition extends deep into the composite metallurgical layer, since it penetrates and occupies the voids of the structural base composition. The distribution of the metal elements through the structural thickness of the composite metallurgical layer according to the invention can be visualized by imaging using a transmission electron microscope (TEM) according to the mapping technique TEM-EDS (Transmission Electron Microscopy and Energy Dispersive X-ray Analysis).
[0031] Using TEM-EDS techniques, it is possible to directly image the distribution of the various essential constituent metals, observing their distribution within the thickness of the composite metallurgical layer and confirming the presence of the anode structure of the present invention, especially when compared with the overall image obtained by HAADF (High Angle Annular Dark Field Transmission Electron Microscopy). Using TEM-EDS mapping techniques, it is possible to visualize each metal element individually within the composite metallurgical layer. In particular, it is easily observed that the cobalt of the cobalt oxide particles is present in a high density concentration (coating) on the outer surface of the composite layer, but it is further evident that the cobalt is present in a low density throughout the depth of the composite layer, as it penetrates into the base composition according to the present invention. Thus, ruthenium, which is present in the catalyst composition at a lower level than the structural base composition, appears in a lower density in the surface regions where the cobalt catalyst density is higher and in a higher density in the regions of the base composition, according to TEM-EDS, while the titanium of the base composition is mainly restricted to that region of the composite layer and shows little movement into the concentration of the surface catalyst composition. Tin is distributed throughout the layer and is present in both the base composition and the antimony-tin matrix of the catalyst composition.
[0032] The distribution and concentration of metal elements throughout the composite metallurgical layer can also be quantitatively measured using TOF-SIMS (Time of Flight Secondary Ion Mass Spectroscopy) technique, which allows mapping of metal concentrations through the depth of the composite metallurgical layer and can also confirm the presence of the structure of the present invention, as shown in Figures 3 and 4, which map the concentrations of titanium, ruthenium, tin, and cobalt through the depth of the composite metallurgical layer of a corresponding sample of the present invention. More specifically, the TOF-SIMS sample was placed on a 1 cm 2 coated electrode for SIMS loading. 2 Prepare the sample by cutting it out and ionizing it with Cs + The TOF-SIMS analysis was performed using ions, current: 3 keV, 20 nA, sputter area: 150 μm × 150 μm, and the detected ion was Cs to minimize any matrix effects. + Adsorbed secondary ions (Cs +-metal) was used. For depth calculation, the depth measurement value is determined after sputtering. A quantitative calculation method is used to calculate the RSF (Relative Sensitivity Factor) by the following formula: Intensity / Concentration=RSF
[0033] The concentration of each metal element is obtained by ICP-MS and used together with the intensity of each element (by depth) by TOF-SIMS to calculate the RSF and derive the depth profile of each metal. In the anode of the first aspect, the cobalt of the catalyst composition is non-uniformly distributed through the thickness of the composite metallurgical layer, with the concentration of cobalt oxide being higher in the composite metal layer adjacent its outer surface than in the composite metal layer adjacent the substrate surface, e.g., as determined by the techniques described above. Such a preferred embodiment is illustrated in Figures 3 and 4, which show the characteristic non-uniform distribution of cobalt through the depth of the composite metallurgical layer. In a further enhanced embodiment of the anode of the first aspect, the composite metallurgical layer further comprises ruthenium oxide distributed throughout or substantially throughout both the base structural composition and the catalyst composition. In particular, the ruthenium oxide is preferably distributed in the matrix of the catalyst composition, more preferably in the preferred catalyst matrix of antimony and tin oxides as described herein above. The inclusion of ruthenium oxide throughout or substantially throughout the composite metallurgical layer further improves the electrical conductivity of the layer, increases the low salt efficiency of the anode, and improves the long term durability of the anode structure.
[0034] Ruthenium oxide may most advantageously be included in the composite metallurgical layer by application as an intermediate layer (or "interlayer") between the application of the structural base composition and the application of the catalyst composition during the method of the second aspect, with subsequent heat treatment of the resulting structure leading to migration of the ruthenium oxide interlayer throughout the composite layer, providing enhanced conductive pathways through the composite layer and other advantages identified above. The structural base composition of all the embodiments of the anode of the first aspect comprises metal oxide compounds of ruthenium, tin and titanium, and preferably consists essentially of metal oxide compounds of ruthenium, tin and titanium, so as to obtain the desired stoichiometric ratio of Ru:Sn. The combination of these three metals is important to obtain the correct morphology of the structural base composition in situ on the anode surface. Other metal oxides or other compounds may also be present as long as they do not adversely affect the morphology of the base composition, but most preferably the structural base composition consists of metal oxide compounds of ruthenium, tin and titanium. In particular, the particular combination of ruthenium, tin, and titanium provides a base structure composition that exhibits a desirable particulate base morphology, resulting in a resilient base structure that is resistant to significant cracking, and preferably free of cracking, onto which a catalyst composition can be applied. In contrast, conventional coating compositions based on, for example, ruthenium and tin typically exhibit a precipitate-like "mud-crack" surface and do not provide the same resilient base for subsequent compositions.
[0035] Furthermore, the particular combination of ruthenium, tin, and titanium in the structural base composition provides improved durability of the anode of the first aspect of the invention as compared to a similar base composition containing only ruthenium and titanium, or only ruthenium and tin. In this regard, the combination of both tin and titanium with ruthenium provides the anode of the invention with improved anode life and improved mechanical adhesion, further contributing to the benefits of the invention. The ruthenium, tin, and titanium oxides of the structural base composition also contribute significantly to the overall stoichiometry of these metals in the composite metallurgical layer of the anode of the first embodiment, and therefore the respective contents of ruthenium, tin, and titanium within the structural base composition should be adjusted according to the techniques in the art to arrive at the overall stoichiometry required for the composite metallurgical layer. However, in practice, when the process conditions of the second aspect of the invention are employed, the metal stoichiometry Ru ≧0.3 (Sn+Ti) ≦0.7By applying a structure-based starting composition having a stoichiometric level of at least 0.3, a suitable total stoichiometry of these metals in the composite metallurgical layer will be reached. With respect to the method of the second aspect, it is important that ruthenium is present in the starting base composition at a stoichiometric level of at least 0.3 in order to obtain the anode and advantages of the present invention. However, one skilled in the art can vary this starting base composition to obtain a particular desired total metal stoichiometry, for example, taking into account any additional contributions of tin or ruthenium in a particular embodiment of the catalyst composition.
[0036] The above-described embodiments of the first aspect of the invention may, in addition to the above-described features, include one or more further components to enhance certain properties of the anode, so long as the overall advantages of the invention are still obtained. For example, in the anode structure of any preceding embodiment, the base structure composition or the catalyst composition or both include a precious catalytic metal (in addition to any palladium, if present), preferably iridium, in the form of its oxide or other catalytically active species, in an amount that provides a total additional precious metal content, preferably an iridium content, of at most 15 atomic %, preferably at most 10 atomic %, more preferably at most 7 atomic % of the total metal atomic content of the composite metallurgical layer. This optional presence of small amounts of precious metal, especially iridium, may be preferable in terms of further enhancing the catalytic performance of the anode, but should be limited according to the objective of the invention to minimize the use of expensive precious metals and rely mainly on cobalt oxide for catalytic activity. Such amounts of precious metals are therefore much less than those typically used when the catalyst composition is based on such metals.
[0037] Alternatively or additionally, the anode composite metallurgical layer of all embodiments further comprises at least one copper compound in an amount to provide a total copper content in the composite metallurgical layer of at most 10 atomic %, preferably at most 2 atomic %, of the total metal atomic content of the composite metallurgical layer; or at least one aluminum compound in an amount to provide a total aluminum content in the layer of at most 30 atomic %, preferably at most 20 atomic %, of the total metal atomic content of the composite metallurgical layer; or at least one nickel compound in an amount to provide a total aluminum content in the layer of at most 15 atomic %, preferably at most 10 atomic %, of the total metal atomic content of the composite metallurgical layer; or more than one of the above. The further presence of copper, aluminum, or nickel in the composite metallurgical layer provides a further increase in catalyst selectivity for the chlorine evolution reaction, as measured, for example, by low salt efficiency. Thus, although copper and / or aluminum and / or nickel may be distributed throughout the composite layer, it is preferred that copper and / or aluminum and / or nickel are introduced in the form of one or more oxide compounds and are present in the catalyst composition.
[0038] Second aspect of the present invention (preparation method) A second aspect is a method for preparing a catalytic anode structure for use in an electrochlorination system, comprising the following sequence of steps: a) providing or obtaining a conductive solid substrate; b) providing on the electrolyte-facing surface of the substrate a conductive metallurgical composition (i), the composition (i) having a total metal stoichiometry of Ru ≧0.3 (Sn+Ti) ≦0.7 applying an electrically conductive metallurgical composition (i) comprising compounds of ruthenium, tin, and titanium in an amount providing c) optionally applying to the metallurgical layer resulting from the application of composition (i) a conductive metallurgical composition (ii) comprising one or more ruthenium compounds; and (d) applying an electrically conductive metallurgical catalyst precursor composition (iii) comprising cobalt oxide crystalline particles to the metallurgical layer resulting from the application of composition (i) or resulting from the application of compositions (i) and (ii), with composition (ii) optionally being applied thereto. Including, the process solvent used to apply the metallurgical composition in steps (b) and (d) and optionally step (c) is a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5; The resulting structure is then dried and then heat treated at a temperature of at least 450 ° C. A method is provided.
[0039] The method of the second aspect of the invention results in a catalytic anode structure as defined in the first aspect of the invention and is a preferred method for preparing the anode of the first aspect. The temperature conditions and process solvents defined in the method of the second embodiment are important to obtain the desired catalytic anode structure. In this method, the obtained structure is heat treated at a temperature in the range of at least 450° C., preferably in the range of 450° C. to 600° C., for example, 450° C. to 550° C. More preferably, the obtained structure is heat treated at a temperature in the range of 475° C. to 525° C., and optimally at a temperature of 500° C. The method of the present invention also requires the use of a specified process solvent for applying the metallurgical composition in steps (b) and (d) and optionally step (c), the process solvent being a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5, preferably in a volume ratio range of 82.5:17.5 to 87.5:12.5. Most preferably, the process solvent is a mixture of isopropanol and water in a volume ratio of 85:15. It has been found that this composition of the process solvent exhibits advantages over similar alcoholic solvents in terms of the dissolving power of the starting compounds used in the method of the second aspect. In addition, it has been found that this composition of the process solvent is advantageous for controlling the surface morphology of the layer formed by the application of the metallurgical composition, both before and after the final heat treatment step, and more preferably contributes in particular to obtaining an aggregate particle morphology of the structure base composition that is free of integrity-weakening cracks. This ability to control the layer morphology is due in particular to the choice of alcohol and the alcohol to water ratio in the process solvent, the control being optimal at a volume ratio of 85:15 (isopropanol:water).
[0040] Preferably, in the method of the present invention, the anode substrate (a) is heated to a temperature in the range of 55-200° C. during steps (b) and (d) and, if present, during step (c), and the resulting structure is then dried at a temperature within the same range. Preferably, heating of the anode substrate to this temperature range is carried out throughout steps (b) and (d) and, if present, during step (c), and the resulting structure is then dried at a temperature within the same range. Optimally, the substrate (a) is heated to a temperature of 100° C. throughout steps (b) and (d) and, if present, during step (c), and the resulting structure is then dried at that temperature.
[0041] The use of a specified process solvent, which is volatile under the conditions, during application step (b) of the method, and heat treatment of the substrate, if present, allows the formation of voids in the structural base layer, which voids can be advantageously penetrated by the catalyst composition (iii) subsequently applied in step (d) (and optional composition (ii) applied in step (c)). The use of a specified process solvent and specified heating of the substrate, if present, during application step (d) (and optional application step (c)), if present, and subsequent heat treatment of the resulting structure also contribute to the formation of advantageous morphology and composition of the resulting composite metallurgical layer on the anode of the present invention. In particular, it has been found that applying metallurgical compositions (i) and (iii) (and composition (ii), if present) to a substrate which has been preferably heated in accordance with the second aspect of the invention enhances the formation of the desired composite metallurgical layer on the anode. Importantly, it has also been found that drying the resulting structure within the same temperature range enhances the formation of the desired morphology, particularly a continuous layer, particularly a continuous layer uninterrupted by mud cracks or other significant through discontinuities.
[0042] Importantly, it has been found that a required final heat treatment of the resulting structure at a temperature of at least 450°C enhances the formation of the desired composite metallurgical layer, particularly by promoting improved mechanical adhesion between the composite metallurgical layer and the anode substrate, and by promoting high selectivity for the chlorine evolution reaction over the oxygen evolution reaction via water splitting. In this regard, in the second aspect of the invention, a final heat treatment in the range of 450-550°C, and in particular an optimum final heat treatment at 500°C, is preferred, with higher selectivity for the chlorine evolution reaction and mechanical adhesion being observed. In the process of the second aspect, the use of the temperature conditions and process solvents defined above in combination with the specified metallurgical contents of starting compositions (i) and (iii) (and optimally (ii), if present) results in the formation on the anode substrate of a composite metallurgical layer having the desired composition and morphology suitable for use as an anode of the first aspect. In the method of the second aspect, the composition (i) applied in step (b) comprises a total metal stoichiometry of Ru ≧0.3 (Sn+Ti) ≦0.7 The composition (i) comprises compounds of ruthenium, tin and titanium in amounts providing a ruthenium content of 0.3 or more stoichiometrically relative to the tin and titanium present in the composition (corresponding to 30 atomic %) in order to reach the desired base structure. It has been found that the durability of the resulting structural base composition, when applied according to the method of the second aspect, is significantly improved when the ruthenium in the starting composition (i) is at or above this level. In addition, ruthenium promotes the overall conductivity of the base structural composition.
[0043] In this regard, the composition (i) applied in step (b) of the method may comprise a composition (i) having a total metal stoichiometry of Ru 0.3 (Sn+Ti) 0.7It is preferred that the composition (i) of the present invention contain an amount of ruthenium, tin, and titanium compound that provides: This level of ruthenium is optimal in composition (i) of the present process, and is believed to result in a particularly efficient and durable anode structure. The presence of a combination of tin and titanium in addition to ruthenium in composition (i) results in the formation of a structure-based composition having the desired morphology of agglomerated particles, and the absence of extensive mud cracking behavior seen in other compositions containing only ruthenium and titanium or only tin, when applied by the method of the second embodiment. In this regard, the minimum level of ruthenium relative to tin and titanium in the starting composition (i) of 30 atomic % also leads, under the conditions of the method, to the formation of a network of agglomerated particles in the resulting structure-based composition morphology, and the absence of cracking behavior. The presence of tin in composition (i) in combination with ruthenium and titanium also contributes significantly to the long-term durability of anodes prepared according to the second aspect, resulting in increased mechanical adhesion between the composite metallurgical layer and the anode substrate. The tin content in composition (i) can be adjusted to provide the resulting anode with the desired overall stoichiometric ratio of Ru:Sn in the final anode structure, and the desired performance in this regard. To optimize these benefits, it is preferred that tin and titanium are present in approximately equal amounts in composition (i). Thus, most preferably, composition (i) applied in step (b) contains a total metal stoichiometry of Ru in composition (i). 0.3 Sn ≧0.3 Ti ≦0.4 , optimally Ru 0.3 Sn 0.35 Ti 0.35 The present invention includes compounds of ruthenium, tin, and titanium in amounts providing
[0044] In all the above embodiments of the second aspect, in addition to the essential compounds of ruthenium, tin, and titanium, trace amounts of other metal compounds may be present, but composition (i) preferably consists essentially of compounds of ruthenium, tin, and titanium, and composition (i) preferably contains a total metal stoichiometry of Ru. 0.3 (Sn+Ti)0.7 , most preferably with a total metal stoichiometry of Ru 0.3 Sn 0.35 Ti 0.35 More preferably, the catalyst comprises compounds of ruthenium, tin, and titanium in amounts providing: In the method of the second aspect, in step (d), composition (iii) is applied to the metallurgical layer resulting from the application of composition (i), or to the metallurgical layer resulting from the application of compositions (i) and (ii), with composition (ii) being optionally applied. Composition (iii) is an electrically conductive metallurgical catalyst precursor composition comprising cobalt oxide crystalline particles of the type described herein above with respect to the first aspect. In this regard, it is preferred that the cobalt oxide crystalline particles in the catalyst precursor composition consist essentially of crystalline cobalt oxide having the formula Co3O4. In one such embodiment, these cobalt oxide crystalline particles may consist of crystalline cobalt oxide having the formula Co3O4. The presence of this crystalline form of cobalt oxide may be confirmed by x-ray diffraction or other conventional crystallographic techniques.
[0045] In another more preferred embodiment, the cobalt oxide crystalline particles in the catalyst precursor composition consist essentially of crystalline cobalt oxide having the formula Co3O4 and further consist essentially of ruthenium at a level of up to 5 atomic % ruthenium based on the total metal atomic content of the crystalline particle, at least a portion of said ruthenium being present on the crystalline particle in the form of a surface decoration. In this latter embodiment, the cobalt oxide crystalline particles in the catalyst precursor composition, in addition to the surface decoration, may further include crystalline regions in which ruthenium is incorporated within the crystal lattice of the cobalt oxide, or forms a mixed metal oxide with cobalt, or both. The limited amount of ruthenium provided in association with the cobalt oxide crystalline particles in the catalyst precursor composition in such embodiments provides the advantage that when applied to the anode in the method of the present invention, it further enhances the properties of the composite metallurgical layer, most notably by improving the selectivity of the catalyst for the chlorine evolution reaction and improving the durability of the anode, particularly in terms of operating life. The ruthenium may be present in the form of an oxide compound or may be present in the form of a metallic element, at least when incorporated within the crystal lattice of the cobalt oxide. In such embodiments, the ruthenium associated with the cobalt oxide catalyst may be present in a total non-stoichiometric proportion approximating a mixture of elemental ruthenium and oxide-bound ruthenium.
[0046] However, it has been found that exceeding the upper limit of 5 atomic % of the ruthenium content associated with the crystalline particles in the catalyst precursor composition leads to a decrease in the efficiency of the chlorine evolution reaction, as manifested by a decrease in the low salt efficiency, particularly in the case of water treatment applications.For this reason, the ruthenium content associated with the cobalt oxide catalyst particles should be limited to the levels described, and it is not advantageous to further increase the ruthenium content in the hope of any further improvement. In all the above embodiments, the catalyst precursor composition preferably consists essentially of cobalt oxide crystalline particles distributed in a mixture with other metal compounds which, when applied by the method of the second aspect, result in a crystalline matrix of other metal oxides in the final catalyst composition of the anode of the invention. It is particularly preferred that such other metal compounds do not substantially or in any amount contain precious metal oxides such as palladium or iridium other than those defined herein for the present invention. In a particularly advantageous embodiment, the method of the second aspect is carried out using, as a catalyst precursor, composition (iii) in which cobalt oxide crystalline particles (preferably as described above) are dispersed in a mixture of antimony and tin compounds, the total molar ratio of cobalt:total antimony and tin in composition (iii) being within the range of 20:80 to 80:20. This combination of antimony and tin compounds in composition (iii) results in a crystalline matrix of antimony and tin oxides in which the crystalline particles of cobalt oxide, when applied by the method of the second aspect, aggregate to give rise to the desired morphology of the composite metallurgical layer.
[0047] In this preferred embodiment, it has also been found that the use of a total molar ratio of cobalt:antimony and tin within the ranges specified for composition (iii) results in increased operational durability of the anode structure resulting from the method of the present invention, as indicated by maintaining a lower overpotential for a longer period of time, as compared to ratios outside the specified ratio ranges. Furthermore, being within the specified ratio ranges increases the efficiency of the resulting catalytic anode for the chlorine evolution reaction. In this regard, the total molar ratio of cobalt:antimony and tin is preferably between 20:80 and 80:20, more preferably between 60:40 and 40:60, with a ratio of 50:50 being most preferred, being optimal for obtaining a resulting anode with high CER efficiency and longer operational life, especially at low overpotential. In the preferred embodiment above, it has also been found that the performance of the resulting anode can be further enhanced when prepared according to the method of the second aspect by using a composition (iii) in which the total ratio of cobalt:antimony and tin is controlled as described above, and further wherein antimony and tin compounds are present in composition (iii) in amounts that provide a total metal stoichiometry of antimony:tin of up to 1:10, preferably up to 1:20. Additionally, by controlling the ratio of antimony to tin in composition (i) within this range, the method of the present invention provides an anode with a further improved efficiency in the chlorine evolution reaction.
[0048] More preferably, in this very advantageous embodiment of the method, the total metal stoichiometry of antimony:tin in composition (iii) is at most 1:50, in particular at most 1:100. The optimal total metal stoichiometry of antimony:tin in composition (iii) for achieving an increased efficiency of the chlorine evolution reaction is 1:200. Composition (iii) most preferably combines the preferred range of the sum of cobalt:antimony and tin ratio with the preferred range of antimony:tin total metal stoichiometry. Such composition (iii) serves as a particularly effective catalyst precursor composition in the process of the second aspect of the invention, leading to the formation of anode structures having a particularly effective combination of efficiency in the chlorine evolution reaction and high durability providing longer operating life at low overpotentials. Thus, in particular in the method of the second aspect, it is preferred that composition (iii) comprises cobalt oxide crystalline particles dispersed in a mixture of antimony and tin compounds, the total molar ratio of cobalt:antimony and tin combined being in the range of 20:80 to 80:20, and the total metal stoichiometric ratio of antimony:tin being at most 1:10, preferably at most 1:20. It is more preferred that composition (iii) comprises cobalt oxide crystalline particles dispersed in a mixture of antimony and tin compounds, the total molar ratio of cobalt:antimony and tin combined being in the range of 40:60 to 60:40, and the total metal stoichiometric ratio of antimony:tin being at most 1:50, preferably at most 1:100. Composition (iii) comprises cobalt oxide crystalline particles dispersed in a mixture of antimony and tin compounds, the total molar ratio of cobalt:antimony and tin combined being 50:50, and most preferably the total metal stoichiometry of antimony:tin being up to 1:100, optimally 1:200 or less, and ideally within the range of 1:200 to 1:250.
[0049] Such highly preferred embodiments of composition (iii) may further comprise preferred embodiments of cobalt oxide crystalline particles described herein above, in particular cobalt oxide crystalline particles consisting essentially of crystalline cobalt oxide having the formula Co3O4, and more preferably the crystalline particles may consist essentially of ruthenium at a level of up to 5 atomic % ruthenium based on the total metal atomic content of the crystalline particles, at least a portion of said ruthenium being present on the crystalline particles in the form of surface decoration. In this latter embodiment, the cobalt oxide crystalline particles in catalyst precursor composition (iii) may further comprise, in addition to the surface decoration, crystalline regions in which ruthenium is incorporated within the crystal lattice of the cobalt oxide or forms a mixed metal oxide with cobalt, or both. Each of compositions (i), (ii), and (iii) for use in the process of the first aspect can be prepared from compounds known in the art for the purpose of metal oxide catalyst preparation and mixed together in the appropriate ratio in the presence of a process solvent in accordance with the teachings of the present invention. Such compounds can include related metal oxide compounds and, where practical, typically other compounds are used that allow for better mixing or suspension and that will be oxidized under the subsequent heat treatment of the process to produce the desired metal oxide in situ.
[0050] Thus, in the process of the second aspect, the compounds of ruthenium, tin and titanium present in composition (i), the compounds of tin and antimony in composition (iii), if present, and the ruthenium compound in optional composition (ii), if present, each comprise compounds other than oxide compounds, and their application of heat in process steps (b) and (d) and optional step (c), if present, followed by drying and heat treatment, preferably thermally decomposes these compounds into one or more of the respective metal oxide or mixed metal oxide compounds within the composite metallurgical layer of the final anode structure. In this regard, the ruthenium, tin and titanium compounds present in composition (i) preferably comprise, and more preferably consist of, their respective halide compounds and / or complexes with acetylacetone, the tin and antimony compounds present in composition (iii) preferably comprise, and more preferably consist of, their respective halide compounds, and the ruthenium present in composition (ii), if applied, preferably comprises, and more preferably consists of, one or more of the corresponding halide compounds or complexes with acetylacetone. Such compounds provide suitable dispersion of the metals in the compositions used in the process, which are then converted under the conditions of the process of the invention to their respective oxides to give rise to the desired anode of the first aspect of the invention.
[0051] The starting composition of the present method may further comprise other metal compounds that provide additional benefits to the resulting anode, as detailed in the first aspect. Thus, the starting composition may further comprise at least one palladium compound in an amount to provide a total palladium content of preferably at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of the starting composition. Preferably, starting composition (iii) further comprises at least one palladium compound in an amount to provide a total palladium content of preferably at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of the starting composition. Composition (iii) may further comprise at least one copper compound, or at least one aluminum compound, or both, in an amount providing composition (iii) with a total copper content of up to 10 atomic %, preferably up to 2 atomic %, based on the total metal atomic content of the composition, or a total aluminum content of up to 30 atomic %, preferably up to 20 atomic %, based on the total metal atomic content of the composition, or a total nickel content of up to 15 atomic %, preferably up to 10 atomic %, based on the total metal atomic content of the composition, or more than one of the above, respectively.
[0052] At least one of compositions (i), (ii), or (iii) may further comprise at least one iridium compound in an amount to provide a total iridium content of up to 15 atomic %, preferably up to 10 atomic %, respectively. These additional metallic species may be introduced via their compounds conventionally used in the art for inclusion in metallurgical coatings. In a further preferred embodiment, the starting composition (iii) does not contain any titanium compounds, and the process of the second aspect results in a titanium-free catalyst composition having the attendant advantages described herein above. In the method of the present invention, the conductive solid substrate consists essentially of a valve metal, preferably titanium, as detailed in the first aspect of the present invention. In the method of the present invention, each metallurgical composition applied in steps (b) and (d) and optional step (c), if present, may be applied sequentially by coating techniques known in the art, such as brush application, roller application, or drawdown application, spray coating by means such as electrospray or pressure spray, dip coating, and curtain coating, where thicker coatings may be applied, if desired, by coating techniques that include multiple passes over the underlying structure. Preferably, each metallurgical composition applied in steps (b) and (d) and optional step (c), if present, is applied sequentially by brush coating in one or more passes over the underlying structure or by spray coating in one or more passes over the underlying structure, however, other conventional techniques can also be used to apply one or more of the metallurgical compositions.
[0053] Third aspect of the present invention (electrochlorination system) In a third aspect, the present invention provides an electrochlorination system comprising an electrolytic anode structure obtainable by the method of the first aspect or of the second aspect, as described above.
[0054] Fourth aspect of the present invention (electrolysis method) In a fourth aspect, the present invention provides an electrolytic method for catalytically generating chlorine gas from an aqueous solution containing chloride ions, comprising the step of passing an electric current through said solution in an electrolytic cell comprising an electrolytic anode structure obtainable by the method of the first aspect or of the second aspect, at the anode chlorine gas is generated from the aqueous solution. In a preferred embodiment of the electrolytic process, the chlorine gas generated by the process is used as a biocide to disinfect water, more particularly, ballast water, or industrial wastewater, or municipal or domestic water, such as recreational water for swimming pools and domestic drinking water. In an alternative preferred embodiment, the process is a chlor-alkali process for producing and recovering chlorine.
[0055] Exemplary embodiments of the present invention 1. Preparation Example Preparation of Exemplary Starting Compositions for the Methods of the Invention 1.A Exemplary starting compositions (i), (ii), and (iii) for use in steps (b), (c), and (d) of the present method were prepared from the following component compounds and liquids available in the art: Crystalline solid compounds: RuCl3.xH2O (commercially available, obtained from Sigma-Aldrich), SnCl4.5H2O (commercially available, obtained from Sigma-Aldrich), SbCl3 (commercially available, obtained from Sigma-Aldrich), PdCl2 (commercially available, obtained from Alfa Aesar), Ru(acac)3 (commercially available, obtained from Sigma-Aldrich; "acac" stands for acetylacetone), and Crystalline cobalt oxide particles, having the chemical formula Co3O4, synthesized according to the procedure outlined in Section 1.D below. liquid: 2-propanol (also called isopropanol, commercially available and obtained from Alfa Aesar); Deionized water, TiCl3 solution (TiCl3 is commercially available and was obtained from Sigma-Aldrich and dissolved to a 12% solution in aqueous hydrochloric acid).
[0056] 1.B Preparation of the Starting Composition (i) of the Method A total metal stoichiometry of Ru for use in the present method to form the structural base composition of a composite metallurgical layer. 0.3 Sn 0.35 Ti 0.35 A preferred composition (i) consisting essentially of compounds of ruthenium, tin, and titanium having the formula: was prepared according to the following sequence: To a 70 mL vial, RuCl3.xH2O (207.6 mg; 1 mmol) and SnCl4.5H2O (409.4 mg; 1.17 mmol) were added. The solid material was dissolved in 2-propanol (17 ml) by vortexing until no metal precursor precipitated on standing. To the resulting solution, 1.5 ml of TiCl3 solution (12% TiCl3 in hydrochloric acid solution, 1.17 mmol) was added dropwise with mechanical stirring at 1,000 rpm. Additionally, 1.5 ml of deionized water was added dropwise to the solution. The resulting solution was aged for 5 hours under ambient conditions with mechanical stirring at 1,000 rpm to produce composition (i) for use in the method of the present invention.
[0057] 1.C Preparation of the starting composition (ii) of the present process A preferred composition (ii) consisting essentially of ruthenium dioxide for use in the present process to form the optional intermediate layer was prepared according to the following sequence. A solvent was prepared by mixing 2-propanol (38.7 ml) and deionized water (7.8 ml). 15.5 ml of the prepared solvent was then placed in a 70 ml vial, to which 115.8 mg (0.29 mmol) of Ru(acac)3 and an additional 2 ml of IPA were added. The as-prepared solution was then sonicated for 20 minutes to produce composition (ii) for use in the method of the present invention.
[0058] 1.D Preparation of the starting composition (iii) of the present process A preferred catalyst precursor composition (iii) consisting essentially of crystalline particles of cobalt oxide for use in the present process as a composition to form the catalyst composition of the composite metallurgical layer was prepared according to the following sequence: a) Synthesis of Co3O4 crystalline particles Co(NO3)26H2O (170 g, 0.584 mol) was dissolved in ethanol (99.9%, 510 ml) in a beaker at room temperature. To this mixture, 1-heptanol (510 ml) was added and the mixture was stirred for 5 minutes. The mixture was transferred to a pressure reactor and heated at 160°C for 7 hours. The resulting mixture was left for 16 hours to cool to room temperature and precipitate the solid product. The resulting supernatant was decanted and the resulting solid product was washed three times with isopropyl alcohol (100 ml). Between each wash, the product was mixed well and then centrifuged at 8500 rpm for 1 hour. In each case, the supernatant was decanted off. Isopropyl alcohol (IPA) was added to a solids content of 12% by weight (the amount of IPA added was calculated from the density of the resulting solution after mixing). The resulting mixture was dispersed using a ball mill with 0.5 mm ZrO2 beads at room temperature for 2 hours at 2000 rpm to obtain a 12 wt% Co3O4 nanoparticle solution. The size of the Co3O4 crystalline particles synthesized above was determined by directly measuring the diameter on transmission electron micrograph images, and was found to be in the range of 3 nm to 7 nm, with a median diameter of 5 nm.
[0059] b) Preparation of composition (iii) A solvent was prepared by mixing 2-propanol (38.7 ml) and deionized water (7.8 ml). In this solvent, SbCl3 (44.7 mg; 0.20 mmol) was dissolved by vortexing. 5 ml of this as-prepared solution was then diluted with an additional 45 ml of the solvent mixture to form a first "antimony solution". 15.5 ml of this antimony solution was then mixed with SnCl4.5H2O (457.8 mg, 1.31 mmol) by vortexing to form an "antimony-tin solution". PdCl2 (4.8 mg; 0.027 mmol) was placed in a 70 ml vial, and the prepared antimony-tin solution was then poured into the vial. In addition, 1 ml of the Co3O4 crystalline particle solution (0.438 mmol) prepared in a) above and 1 ml of 2-propanol were each added to the solution. Finally, the mixture was sonicated for 20 minutes to produce composition (iii) for use in the method of the present invention. This composition (iii) comprises Co3O4 crystalline particles incorporated with palladium at a level of 1 atomic % in a solution of antimony and tin compounds, with an antimony:tin molar ratio of 1:247 and a total metal stoichiometry of cobalt:antimony and tin combined of 50:50.
[0060] Preparation of the catalytic anode of the present invention by the method of the present invention An anode according to the first aspect of the invention was prepared according to the method of the second aspect of the invention as follows. A titanium mesh was prepared as an anode substrate, which was heated to a temperature of 100° C. using a heating plate after cleaning. At this temperature, the composition (i) prepared above was applied to the heated substrate surface by brush coating. The resulting coated sample was kept at 100° C. for 1 minute, the substrate was turned over, the back side was coated again, and the substrate was kept at 100° C. for 1 minute. The coated sample was then transferred to a 500° C. oven and kept there for 5 minutes. The coated sample was then returned to the 100° C. hot plate and the coating and heat treatment steps were repeated. This brush coating of the substrate surface with composition (i) was repeated four more times, resulting in a total of five brush passes over the surface to be coated. The resulting structure was then further brush-coated with composition (ii) prepared above as described above, for a total of 5 brush passes over the surface. The resulting structure was then further brush-coated with composition (iii) prepared above, for a total of 10 brush passes over the surface with this catalyst precursor composition. After these coating steps, the resulting coated structure was dried at the same temperature. The dried resultant structure was then subjected to a final heat treatment in an oven at 500° C. for 1 hour, followed by slow cooling in the oven for 8 hours to obtain the anode structure of the present invention.
[0061] Three further examples were prepared following the general procedure above, but in order to isolate the metal compositions of the resulting composite metallurgical layer, a glass substrate was used instead of the titanium substrate of the above examples, and compositions (i), (ii), and (iii) were applied by spray coating. In the case of Example 1 below, three spray passes were used to apply each of compositions (i), (ii), and (iii), composition (i) was sprayed at a rate of 300 μL / min, and compositions (ii) and (iii) were sprayed at a rate of 600 μL / min. In the case of Example 2 below, again three spray passes were used to apply each of compositions (i) and (ii), and six spray passes were used to apply composition (iii), compositions (i) and (ii) were sprayed at a rate of 300 μL / min, and composition (ii) was sprayed at a rate of 600 μL / min. In the case of Example 3 below, again three spray passes were used to apply each of compositions (i), (ii), and (iii), with compositions (i) and (ii) sprayed at a rate of 600 μL / min and composition (iii) sprayed at a rate of 300 μL / min. The resulting composite metallurgical layers were then each analyzed multiple times using ICP-MS techniques to provide the following metal compositional information in atomic % of the total metal atomic content: [Table 1] [Table 2] [Table 3]
[0062] In each case, the resulting composite metallurgical layer contained cobalt as the major metallic component, accounting for an average of at least 65 atomic % of the total metal atomic content of the composite metallurgical layer. The average total metal stoichiometric ratio of cobalt to total tin and antimony in each case provided a value within the most preferred range of 3:1 to 5:1, and the total metal stoichiometric ratio of antimony:tin in each case was also within the preferred ratio range for this feature, with samples exhibiting values of 1:75, 1:84, and 1:31, respectively. The total stoichiometric ratio of ruthenium:tin in the composite metallurgical layer was also within the most preferred range of 1:≧5 for this feature, with 1:8, 1:15, and 1:6, respectively, in each case. FIG. 4 provides a typical concentration-depth profile of the metal distribution through the thickness of a composite metallurgical layer prepared in situ according to the method described above, in which cobalt oxide exhibited a favorable non-uniform distribution through the thickness of the composite metallurgical layer, with the cobalt oxide being higher adjacent the outer surface.
[0063] 2. Performance examples The performance and advantages of the anode of the present invention were demonstrated using the following experimental techniques. Chlorine Evolution Reaction (CER) Efficiency Test: The faradaic efficiency of the electrolytic cell provides an important indicator of the efficiency of the catalytic anode for the CER reaction. An electrolytic cell using a counter electrode (cathode) and a working electrode (anode according to the invention) was set up as follows. 5×15cm 2 The Ti mesh counter electrode was etched in 2.0 M sulfuric acid at 60° C. for 1 h until the etching solution turned pale purple. The etched Ti mesh was then sonicated several times in 95% pure ethanol for 10 min. The rinsed Ti mesh was blown dry with nitrogen gas. The dried counter electrode was masked with silicon tape and electroplating tape to obtain a 5×5 cm 2 left the area.
[0064] Anodes prepared according to the present invention were also masked with silicone tape and electroplating tape to form 1×5 cm 2Masking the electrodes helped to concentrate the current in the limited areas of the electrodes exposed to the electrolyte, thus increasing the current density and accelerating the test. The electrolysis cell was assembled by attaching a masked counter electrode to one side of an electrode frame and a working electrode to the other side of the frame, with a portion of the frame at the bottom end of both electrodes maintaining a 5 mm gap between the electrodes. The test cell was constructed and operated under the following conditions. a) 500 ml of 20 mM NaCl solution was poured into a 500 ml beaker. The electrode cell assembled above was placed in the beaker, and two electric wires were connected to the working electrode and the counter electrode, respectively. b) The solution was stirred at 300 rpm using a magnetic stir bar. The attached potentiostat was then switched to 40 mA / cm for 1 min under 300 rpm stirring conditions. 2 The device was operated in chronopotentiometry mode at 400 rpm. c) After 1 minute of operation, the active chlorine concentration was measured and compared to the theoretical concentration obtained from the initial chloride ion concentration to determine the faradaic efficiency (FE) of the cell incorporating the working electrode (anode of the present invention).
[0065] Active chlorine concentration was measured by one of two interchangeable methods described below. Measurement of active chlorine concentration by DPD colorimetry In this method, the DPD vial was washed with DI water until initial testing confirmed that no residual active chlorine was present in the test vial. After the electrolysis cell was operated for 1 minute, the solution was stirred at 600 rpm for 1 minute to create a completely homogenous test solution. 1 ml of this well-mixed solution was then diluted 1 in 10 with 20 mM NaCl solution in a DPD vial to bring the test solution volume to 10 ml. DPD reagent was then added to the DPD vial and the vial was vortexed for 10 seconds. The active chlorine concentration was then measured with a DPD pocket colorimeter and the amount of active chlorine produced was divided by the theoretical active chlorine production to calculate the faradaic efficiency (FE).
[0066] Measurement of active chlorine concentration by iodometric titration After the electrolysis cell was operated for 1 minute, the solution was stirred at 300 rpm to produce a homogenous solution. 1.6 g of KI (potassium iodide) was then added to the beaker containing the solution. After the KI was added, the solution turned a light yellow color. After 4 ml of glacial acetic acid was added to the solution, the solution turned a light orange color. After 4 ml of starch solution was added to the beaker, the solution turned a deep blue color. The deep blue solution was then titrated with 0.02 N sodium thiosulfate until the solution became colorless, and the amount of active chlorine produced was estimated from the titration amount of sodium thiosulfate added. Again, the faradaic efficiency was calculated by dividing the amount of active chlorine produced by the theoretical active chlorine production.
[0067] Chlorine Evolution Reaction (CER) Life Test: The faradaic efficiency of the electrolytic cell, measured periodically over long-term testing, provides an important demonstration of the life of the catalytic anode and therefore of the durability of the anode for the CER reaction. A rapid increase in FE is an indication of anode degradation and, in the case of durability for CER, indicates that a limit is being reached. An electrolytic cell with counter and working electrodes was constructed as described above. For purposes of accelerating the test, the working electrode (anode) was placed 1 cm 2 The area was masked to concentrate the current density. Masking was performed by applying a silicon tape and then applying an electroplating tape on top of it. In addition, before connecting, the top of the working electrode was polished back to the metal substrate. a) 1 liter of 0.6M NaCl solution was poured into a beaker surrounded by a cooling jacket, and the test solution was maintained at 15° C. After allowing the temperature to stabilize for 1 hour, the electrode cell assembled above was placed in the beaker, and two wires were connected to the working electrode and counter electrode, respectively. b) The solution was stirred at 300 rpm using a magnetic stir bar. The attached potentiostat was then turned on at 500 mA / cm under 300 rpm stirring. 2 The device was operated in chronopotentiometry mode until an increase of more than 12 V was recorded, which marked the duration of the experiment. c) During operation, the cell potential was repeatedly measured and plotted over time to report the CER potential over the life test duration and to identify the degradation point where the potential increased so rapidly that it exceeded the useful life of the anode (taken as the point where a voltage above 12V was recorded).
[0068] Mechanical Adhesion Test The mechanical adhesion of the metallurgical surface layer of the anode was evaluated by the following method: A piece of 3M electroplating tape, prepared as detailed above, was applied over the unmasked portion of the working electrode (the anode being tested). Light pressure was applied with a pipette tip to loosen the tape and allow it to adhere firmly to the coated electrode surface. The tape was then removed and the extent of metallurgical coating residue remaining on the adhesive surface of the removed tape was visually evaluated as a measure of the coating adhesion strength to the electrode substrate. More residue on the removed tape indicates poorer residual adhesion to the substrate. Acid Stability Test A 5% by weight hydrochloric acid solution was prepared by diluting concentrated hydrochloric acid with deionized water to the required amount. The anode to be tested was cut to a size of 2 cm x 1 cm and placed in a 10 ml vial, to which 5 ml of 5% hydrochloric acid solution was added so that the anode sample was completely immersed. The color of the sample and the acid solution were observed over time.
[0069] 2.1 Benefits of the structural base composition of the present invention The structure-based composition of the anode of the invention may be prepared in a related method according to the second aspect of the invention by providing composition (i) with an overall metal stoichiometry of Ru ≧0.3 (Sn+Ti) ≦0.7 The importance of these defined features in the process of the present invention was demonstrated as follows.
[0070] 2.1(a) The necessity for ruthenium molar metal stoichiometry to be 0.3 or greater: In Figure 5 the results of CER life tests carried out according to the test method described above are reported. In each case the working electrode (the anode under test) was prepared similarly to the preparation method shown in section 1 of the Examples, but the substrate was coated with only the base composition (i), omitting compositions (ii) and (iii). Three comparative examples of this type were prepared by varying the amount of ruthenium added to composition (i), while maintaining a 1:1 stoichiometric ratio of the tin and titanium components as the balance of each composition. As shown in Figure 5, the CER lifetime results indicate that maintenance of low overpotentials over long periods of time could not be achieved when ruthenium was present at stoichiometric levels below 0.3. Therefore, the specified stoichiometry, where ruthenium is present at a stoichiometric level of at least 0.3, is required for composition (i) to avoid the structure-based composition compromising the fundamental efficiency and durability of the catalytic anode for CER reaction. This ruthenium stoichiometry ensures that the desired morphology of the structure-based composition is obtained as a layer of aggregated particles interspersed with voids, onto which the catalyst composition can then be advantageously applied. The ruthenium stoichiometry of 0.3 in composition (i) ensured that the resulting structure exhibited a well-defined crystalline structure in XPS and well-defined connected particles when imaged using SEM.
[0071] 2.1(b) Essentiality of Ru / Tin / Titanium Ternary Base Composition: FIG. 6 shows the results of a CER life test performed according to the test method described above. In each case, the working electrode (the anode under test) was prepared using a preparation method similar to that shown in Example section 1, where the substrate was coated with base composition (i) and catalyst precursor composition (iii), and optional composition (ii) was omitted. Each example was prepared using the same catalyst precursor composition (i) of the preferred type prepared in Example section 1, consisting of crystalline Co3O4 in a mixture of antimony and tin compounds further incorporating 5 atomic % ruthenium and 1 atomic % palladium. However, the underlayer base composition in these tests was varied. One example (of the present invention) was prepared using composition (i) of the type also illustrated in section 1 above. This composition had a total metal stoichiometry of Ru 0.3 Sn 0.35 Ti 0.35 Two comparative examples were prepared by modifying composition (i) to exclude either the titanium or tin compounds, while maintaining ruthenium at a total metal stoichiometry of 0.3. Thus, a series of tests compared the effect of combining ruthenium with tin and / or titanium, at equal ruthenium content. As shown in Figure 6, the CER lifetime results indicate that the ternary combination of ruthenium, tin, and titanium results in the maintenance of low overpotential for a much longer period in the presence of the same catalyst composition of the present invention. Comparative examples lacking either tin or titanium resulted in shorter lifetimes and did not provide the same advantageous performance.
[0072] Mechanical adhesion tests were also carried out to compare anodes fabricated with ternary metallic composition (i) according to the invention with a comparative example in which the bimetallic composition (i) contained only ruthenium and tin. Superior mechanical adhesion of the metallurgical coating to the substrate surface was observed for the present invention, as evidenced by a lower degree of coating residue visible on the removed adhesive tape. SEM examination of the base coating after application also revealed extensive mud cracking on the precipitate-like outer surface of the base coating for the ruthenium / tin comparative base composition, as shown in Figure 7. In contrast, the base coating made with the ternary base composition of the present invention exhibited a coating of agglomerated particles interspersed with voids. The lifetime advantage of the presence of the structural base layer of the present invention for an electrode whose catalytic layer is formed of Co3O4 crystalline nanoparticles ("NPs") doped with a ruthenium compound is shown in Figure 8. The cell potential over the lifetime of the electrode started at a lower level and showed a significantly slower rate of increase (indicative of an increased overpotential) when a structural base layer was additionally present as an intermediate layer between the electrode substrate and the catalytic composition.
[0073] 2.2 Additional advantages of optional composition (ii) of the present invention The optional intermediate layer provided by applying composition (ii) in a preferred method embodiment of the present invention provides further improvement in the final anode properties. Figure 9 shows a comparison of lifetime between two anodes of the present invention. Both anodes shared the same preferred structural base composition, but one had ruthenium incorporated in the catalyst composition according to the exemplary embodiment in section 1 above, while the other had ruthenium instead incorporated as RuO2 in the optional intermediate layer composition (ii). The latter anode showed improved lifetime in that it maintained a lower potential for a longer period of time.
[0074] 2.3 Benefits of the catalytic composition of the present invention The importance of catalyst composition to performance is discussed below. 2.3(a) Inclusion of Preferred Tin and Antimony Oxide Matrices in the Catalyst Composition The advantage of having tin and antimony present in the specified stoichiometric ratios is illustrated in Figures 10 and 11. Again, similar anodes were prepared according to the examples in Section 1 above, but using catalyst compositions with different tin and antimony contents, as shown in the figures. In each case, life or CER efficiency tests were performed and (over)potentials were compared over time. As shown in Figure 10, the total metal stoichiometric ratio of cobalt:antimony and tin combined in composition (iii) affects the life of the anode. Anode structures fabricated from catalyst precursor compositions in which the ratio is in the range of 20:80 to 80:20, preferably 50:50, show improved durability in terms of maintaining a low potential over a longer operating life. The 50:50 molar ratio was the best. As shown in Fig. 11(a), the total metal stoichiometry Ru 0.3 Sn 0.35 Ti 0.35In the electrodes of the present invention obtained from the structural base composition (i) consisting of compounds of ruthenium, tin, and titanium having the formula: and various catalyst precursor compositions (iii) comprising Co3O4 crystalline particles in a solution of various antimony and tin compounds, the electrodes obtained from the examples in which the antimony and tin compounds are present in the composition (iii) in an amount providing a total metal stoichiometry of antimony:tin up to 1:20 show the greatest advantage in CER efficiency as measured by Faraday Efficiency (FE) using the method detailed hereinbefore, with the advantage increasing as the ratios go from 1:20, 1:50, 1:100, and 1:200, the latter being the most highly effective composition (iii) resulting in the most efficient anode. As FIG. 11(b) shows, the life of electrodes in which antimony and tin compounds were present in composition (iii) in amounts to provide a total metal stoichiometry of antimony:tin up to 1:20 showed improvement compared to examples in which the antimony:tin ratio was 1:3 or 1:6.5.
[0075] 2.3(b) Inclusion of Palladium Oxide in the Catalyst Composition In further experiments, the anode was directly coated with catalytic composition (iii) according to the invention comprising cobalt oxide particles, ruthenium oxide, and oxides of tin and antimony, and the effect of introducing palladium as an additional component was evaluated. The results are shown in the table below, and show that the preferred inclusion of a small amount of palladium in the catalytic composition improves efficiency. [Table 4]
[0076] 2.3(b) Inclusion of iridium in catalyst compositions Additionally, electrodes were prepared generally according to the preparation methods set forth in Section 1, but using different stoichiometric ratios of cobalt:antimony plus tin combined, and omitting palladium from catalyst precursor composition (iii) and introducing iridium instead to demonstrate the benefits resulting from the inclusion of this other metal. These examples are shown in the table below.
[0077] In each case, the faradaic efficiency was measured in 20 mM NaCl solution according to the method described above. The results demonstrate the additional efficiency advantage obtained by including low levels of iridium in the electrodes of the invention. [Table 5]
[0078] The above examples demonstrate the high performance of certain embodiments of the present invention.
Claims
1. 1. A catalytic anode structure for use in an electrochlorination system comprising an electrically conductive solid substrate having an electrically conductive composite metallurgical layer overlying a surface facing an electrolyte, the layer comprising: a structural base composition coating the substrate surface, the structural base composition having the form of aggregate particles interspersed with voids and comprising metal oxide compounds of ruthenium, tin, and titanium; and a catalyst composition comprising cobalt oxide crystalline particles distributed on an upper surface of the structural base composition and within the voids; Including, the cobalt is present in an amount of at least 12.5 atomic % of the total metal atomic content of the composite metallurgical layer, and the ruthenium and tin are present in the composite metallurgical layer in amounts that provide a total metal stoichiometric ratio of Ru:Sn of 1:> 1 based on the total content of ruthenium and tin in the composite metallurgical layer; the outer surface of the composite metallurgical layer having the form of a continuous coating of agglomerated particles; Catalytic anode structure.
2. 2. The anode structure of claim 1, wherein the cobalt is present in an amount of at least 40 atomic % of the total metal atomic content of the composite metallurgical layer, and the ruthenium and tin are present in the composite metallurgical layer in amounts providing a total metal stoichiometric ratio of Ru:Sn of 1:≧5 based on the total content of ruthenium and tin in the composite metallurgical layer.
3. The cobalt oxide crystalline particles in the catalyst composition have the chemical formula Co 3 O 4 3. The anode structure of claim 1 or claim 2, consisting essentially of a crystalline cobalt oxide having a structure of
4. The anode structure according to any one of claims 1 to 3, wherein the catalytic composition further comprises one or more precious metals or compounds thereof, preferably ruthenium or its oxide.
5. The cobalt oxide crystalline particles in the catalyst composition have the chemical formula Co 3 O 4 5. The anode structure of claim 4, wherein the anode structure consists essentially of crystalline cobalt oxide having a cobalt content of about 100% by mass and further consists essentially of ruthenium or an oxide thereof at a level of up to 5 atomic % ruthenium based on the total metal atomic content of said crystalline particles, at least a portion of said ruthenium being present in the form of a surface decoration on said crystalline particles.
6. 6. The anode structure of claim 5, wherein the cobalt oxide crystalline particles in the catalyst composition further include crystalline domains in which ruthenium is incorporated within the crystal lattice of the cobalt oxide, or forms a mixed metal oxide with cobalt, or both.
7. 7. The anode structure of any one of claims 1 to 6, wherein the catalyst composition comprises cobalt oxide crystalline particles within a crystalline matrix of oxides of antimony and tin, the catalyst composition being present on the top surface and within the voids of the structural base composition.
8. 8. The anode structure of claim 7, wherein the total metal stoichiometry of cobalt:antimony and tin combined in said composite metallurgical layer is in the range of 2:1 to 9:
1.
9. 9. The anode structure of claim 7 or 8, wherein the antimony and tin compounds are present in the composite metallurgical layer in an amount to provide a total metal stoichiometry of antimony:tin in the range of 1:5 to 1:200, preferably in the range of 1:5 to 1:
100.
10. 10. The anode structure of any one of claims 4 to 9, wherein the composite metallurgical layer further comprises at least one palladium compound in an amount providing the composite metallurgical layer with a total palladium content of at most 7 atomic %, preferably at most 3 atomic %, of the total metal atomic content of the composite metallurgical layer.
11. An anode structure according to any one of claims 1 to 10, wherein the conductive solid substrate consists essentially of a valve metal, preferably titanium.
12. 12. The anode structure of claim 1, wherein the cobalt of the catalytic composition is non-uniformly distributed through a thickness of the composite metallurgical layer, and wherein a concentration of cobalt oxide is greater in the composite metallurgical layer adjacent an outer surface of the composite metallurgical layer than in the composite metallurgical layer adjacent the substrate surface.
13. 13. The anode structure of any one of claims 1 to 12, wherein the composite metallurgical layer comprises ruthenium oxide distributed throughout or substantially throughout both the base structural composition and the catalyst composition.
14. The anode structure according to any one of claims 1 to 13, wherein the structural base composition consists of metal oxide compounds of ruthenium, tin and titanium.
15. 15. The anode structure of any one of claims 1 to 14, wherein the base structure composition or the catalyst composition or both further comprise iridium in the form of its oxide or other catalytically active species in an amount to provide a total iridium content of up to 15 atomic %, preferably up to 5 atomic %, of the total metal atomic content of the composite metallurgical layer.
16. 16. The anode structure of any one of claims 1 to 15, wherein the composite metallurgical layer further comprises at least one copper compound in an amount to provide in the composite metallurgical layer a total copper content of at most 10 atomic %, preferably at most 2 atomic %, of the total metal atomic content of the composite metallurgical layer; or at least one aluminum compound in an amount to provide in the layer a total aluminum content of at most 30 atomic %, preferably at most 20 atomic %, of the total metal atomic content of the composite metallurgical layer; or at least one nickel compound in an amount to provide in the layer a total nickel content of at most 15 atomic %, preferably at most 10 atomic %, of the total metal atomic content of the composite metallurgical layer; or more than one of the above.
17. The anode structure of any one of claims 1 to 16, wherein the outer surface of the composite metallurgical layer has the form of a continuous, non-cracked coating of agglomerated particles.
18. The anode structure of any one of claims 1 to 17, wherein the catalytic composition of the composite metallurgical layer does not include titanium or compounds thereof.
19. A method for preparing a catalytic anode structure for use in an electrochlorination system comprising the following sequence of steps: a) providing or obtaining a conductive solid substrate; b) providing on the electrolyte-facing surface of said substrate a conductive metallurgical composition (i), said composition (i) having a total metal stoichiometry of Ru ≧0.3 (Sn+Ti) ≦0.7 applying said conductive metallurgical composition (i) comprising compounds of ruthenium, tin, and titanium in amounts providing c) an optional application step, in which a conductive metallurgical composition (ii) comprising one or more ruthenium compounds is applied to the metallurgical layer resulting from the application of composition (i); and (d) applying an electrically conductive metallurgical catalyst precursor composition (iii) comprising cobalt oxide crystalline particles to the metallurgical layer resulting from the application of composition (i), or to the metallurgical layer resulting from the application of compositions (i) and (ii) when composition (ii) is optionally applied. Including, In steps (b) and (d) and optional step (c), the process solvent used to apply the metallurgical composition is a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5; The resulting structure is then dried and then heat treated at a temperature of at least 450° C. method.
20. 20. The method of claim 19, wherein the substrate (a) is heated to a temperature in the range of 50 to 200° C. during steps (b) and (d), and, if present, step (c), and the resulting structure is then dried at a temperature in the same range.
21. 21. The method of claim 20, wherein the substrate (a) is heated to a temperature of 100° C. during steps (b) and (d), and, if present, step (c), and the resulting structure is then dried at that temperature.
22. The method according to any one of claims 19 to 21, wherein after drying, the heat treatment temperature is in the range of 450 to 550°C.
23. The method according to any one of claims 19 to 21, wherein the heat treatment temperature is 500°C.
24. 24. The method of any one of claims 18 to 23, wherein the process solvent used to apply the metallurgical composition in steps (b) and (d) and optional step (c) is a mixture of isopropanol and water in a volume ratio range of 85:
15.
25. 25. The method of any one of claims 19 to 24, wherein each metallurgical composition applied in steps (b) and (d) and optional step (c), if present, is applied sequentially by brush coating in one or more passes over the underlying structure.
26. 25. The method of any one of claims 19 to 24, wherein each metallurgical composition applied in steps (b) and (d) and optional step (c), if present, is applied sequentially by spray coating in one or more passes over the underlying structure.
27. The composition (i) applied in step (b) comprises a total metal stoichiometry of Ru 0.3 (Sn+Ti) 0.70 The method of any one of claims 19 to 26, comprising compounds of ruthenium, tin, and titanium in amounts providing
28. The composition (i) applied in step (b) comprises a total metal stoichiometry of Ru 0.3 Sn 0.35 Ti 0.35 28. The method of claim 27, comprising the compounds of ruthenium, tin, and titanium in amounts providing.
29. The cobalt oxide crystalline particles in the composition (iii) applied in step (d) have the chemical formula Co 3 O 4 The method of any one of claims 19 to 28, wherein the crystalline cobalt oxide has the formula:
30. 30. The method of claim 29, wherein the cobalt oxide crystalline particles in composition (iii) further consist essentially of ruthenium at a level of up to 5 atomic % ruthenium, based on the total metal atomic content of the crystalline particles, at least a portion of the ruthenium being present on the crystalline particles in the form of a surface decoration.
31. 31. The method of claim 29 or claim 30, wherein the cobalt oxide crystalline particles in composition (iii) further comprise crystalline domains in which some ruthenium is incorporated within a crystal lattice of the cobalt oxide, or some ruthenium forms a mixed metal oxide with cobalt, or both.
32. 32. A method according to any one of claims 19 to 31, wherein in composition (iii) applied in step (d), the cobalt oxide crystalline particles are dispersed within a mixture of antimony and tin compounds, and the total metal stoichiometric ratio of cobalt:antimony and tin combined in composition (iii) is in the range of 20:80 to 80:20, preferably 50:
50.
33. 33. The method of claim 32, wherein in composition (iii), the antimony and tin compounds are present in composition (iii) in amounts providing a total metal stoichiometric ratio of antimony:tin of up to 1:10, preferably up to 1:
20.
34. 34. The method of claim 33, wherein in composition (iii) applied in step (d), the compounds of antimony and tin are present in amounts that provide composition (iii) with a total metal stoichiometric ratio of antimony:tin of 1:200 or less.
35. 35. The method according to any one of claims 19 to 34, wherein said composition (iii) further comprises at least one palladium compound in an amount providing composition (iii) with a total palladium content of preferably at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of composition (iii).
36. 36. The method of any one of claims 19 to 35, wherein the compounds of ruthenium, tin and titanium present in composition (i), the compounds of tin and antimony in composition (iii), if present, and the ruthenium compound present in optional composition (ii) each comprise compounds other than oxide compounds, and the heat treatment thereof in steps (b) and (d) and optional step (c), if present, the application of heat thereto, thermally decomposes these compounds into one or more of their respective metal oxide or mixed metal oxide compounds within the composite metallurgical layer of the final anode structure.
37. 37. The method according to claim 36, wherein the compounds of ruthenium, tin and titanium present in composition (i) comprise, preferably consist of, their respective halide or sulphate compounds, and / or complexes with acetylacetone, and the compounds of tin and antimony in composition (iii), if present, comprise, preferably consist of, their respective halide or sulphate compounds, and ruthenium present in composition (ii), when applied, comprises, preferably consists of, its respective halide compound or complex with acetylacetone.
38. 38. The method of any one of claims 19 to 37, wherein composition (iii) further comprises at least one copper compound, or at least one compound of aluminum, or at least one compound of nickel, or more than one of the above, in an amount to provide composition (iii) with a total copper content of up to 10 atomic %, preferably up to 2 atomic %, based on the total metal atomic content of composition (iii), or a total aluminum content of up to 30 atomic %, preferably up to 20 atomic %, based on the total metal atomic content of composition (iii), or a total nickel content of up to 15 atomic %, preferably up to 10 atomic %, based on the total metal atomic content of composition (iii), or more than one of the above.
39. 39. The method of any one of claims 19 to 38, wherein at least one of compositions (i), (ii), or (iii) further comprises at least one iridium compound in an amount to provide a total iridium content of up to 15 atomic %, preferably up to 10 atomic %, respectively, based on the total metal atomic content of the composition.
40. A method according to any one of claims 19 to 39, wherein the conductive solid substrate consists essentially of a valve metal, preferably titanium.
41. An electrochlorination system comprising an electrolytic anode structure according to any one of claims 1 to 18 or obtainable by the method according to any one of claims 19 to 40.
42. 41. An electrolytic process for generating chlorine gas from an aqueous solution containing chloride ions, comprising the step of passing an electric current through said solution in an electrolytic cell comprising an electrolytic anode structure obtainable by the method according to any one of claims 1 to 18 or any one of claims 19 to 40, wherein chlorine gas is generated from said aqueous solution at said anode.
43. 43. The electrolysis process of claim 42, wherein the evolution of chlorine gas from the aqueous solution is facilitated by catalytic action of the composite metallurgical layer overlying a surface of the anode.
44. 44. The electrolytic process according to claim 42 or 43, wherein the chlorine gas generated by the process is used as a biocide for disinfecting water.
45. 45. The electrolysis method of claim 44, wherein the chlorine gas is used to disinfect ballast water, or industrial or municipal wastewater.
46. 44. An electrolytic process according to claim 42 or 43, wherein the process is a chlor-alkali process for the production and recovery of chlorine.